PENERAPAN MODEL TGT BERBASIS TEKA-TEKI SILANG UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA KELAS IV PADA MATERI PERUBAHAN WUJUD BENDA DI SD MUHAMMADIYAH PLUS - Farida, Yeni; Fadilah, Yulina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study describes the implementation of the Teams Games Tournament (TGT) model combined with Crossword Puzzle (TTS) media and its effect on the critical thinking skills of fourth-grade students in learning about changes in the states of matter at SD Muhammadiyah Plus, Probolinggo Regency. The study employed a descriptive qualitative approach with a case study design. Data were collected through observations, interviews with teachers and students, and documentation, then analyzed interactively with validity checks through triangulation, member checking, and peer debriefing. The results show that the integration of TGT–TTS increased students’ engagement and participation and strengthened their critical thinking skills, as reflected in their ability to ask relevant questions, provide logical reasons, and draw conclusions. The crossword puzzle media helped students understand concepts, while the competitive element in TGT increased learning motivation. The novelty of this study lies in the systematic integration of TGT and crossword puzzles in this topic through procedures that are practical and easy to replicate in elementary schools. The implications include recommendations for activity design, crossword puzzle instruments, and assessment guidelines to support the improvement of critical thinking skills.